Sustainability strategies of the company TimorL: extending the applicability of legitimacy theory - Eugénio, T.; Lourenço, I.; Morais, A. (Management of Environmental Quality: An International Journal, 2013)
Purpose – This study aims to identify the legitimacy strategies employed by one of the largest Portuguese cement companies to defend and downplay its sustainability performance and activities related to two major controversies involving the company: co?incineration and the location of the Outão plant. Design/methodology/approach – A single case study methodology is employed for the empirical research. Sustainability reports were analysed in order to identify TimorL's sustainability disclosure practices, and semi?structured interviews were conducted to complement the case analysis. This paper emphasises legitimacy theory and legitimacy repair strategies that were identified by Suchman. Findings – Legitimacy strategies, including “don’t panic”; “create monitors”; “justify”; “disassociate” and “explain”, were identified in the actions TimorL took after the above?mentioned controversies. The company initiated a series of actions to respond to the company's “crisis”. The conclusions of the study support the argument that sustainability strategies remain a powerful legitimacy tool. Originality/value – The paper adds to the scarce research available on the sustainability disclosure and practices of companies by providing new empirical data. It contributes to a better understanding of how companies behave when they are faced with legitimacy gaps and how they act to restore their legitimacy.